Habitus and Personal Trust as a Strategy to Drive Community Participation in the Implementation of Government Policy - Wawan Edi Kuswandoro (Universitas Medan Area, 2023)
This article aims to explore the experiences of the people of Kedunggaleng village, Wonoasih District, Probolinggo City, East Java in implementing government policies in the field of sanitation in the